The origin of the solvent dependence of fluorescence quantum yields in dipolar merocyanine dyes. Issue 48 (4th December 2019) - Hoche, Joscha; Schulz, Alexander; Dietrich, Lysanne Monika; Humeniuk, Alexander; Stolte, Matthias; Schmidt, David; Brixner, Tobias; Würthner, Frank; Mitric, Roland
Abstract : An increasing activation energy barrier to a conical intersection was identified as the reason for higher fluorescence lifetimes and quantum yields for merocyanines in polar solvents. Abstract : Fluorophores with high quantum yields are desired for a variety of applications. Optimization of promising chromophores requires an understanding of the non-radiative decay channels that compete with the emission of photons. We synthesized a new derivative of the famous laser dye 4-dicyanomethylen-2-methyl-6- p -dimethylaminostyryl-4 H -pyran (DCM ), i.e., merocyanine 4-(dicyanomethylene)-2- tert -butyl-6-[3-(3-butyl-benzothiazol-2-ylidene)1-propenyl]-4 H -pyran (DCBT ). We measured fluorescence lifetimes and quantum yields in a variety of solvents and found a trend opposite to the energy gap law. This motivated a theoretical investigation into the possible non-radiative decay channels. We propose that a barrier to a conical intersection exists that is very sensitive to the solvent polarity. The conical intersection is characterized by a twisted geometry which allows a subsequent photoisomerization. Transient absorption measurements confirmed the formation of a photoisomer in unpolar solvents, while the measurements of fluorescence quantum yields at low temperature demonstrated the existence of an activation energy barrier.